Politicization of volunteering in co-production between the public and the voluntary sector: “We should incorporate the idea of the village pond” - Fehsenfeld, Michael (Politica. Tidsskrift for politisk videnskab, 2019)
It is widely acknowledged that the substance of collaboration between public sector and third sector has changed over the last decades. But how does this change affect the understanding of concepts like volunteering, citizen and the relation between state and citizens? This article explores political discourses regarding the relation between the two sectors. The theoretical outset is in anthropology of policy and its understanding of policy as a construing praxis that produces and defines meaning of and in the social world. The empirical data consists of 30 interviews with local politicians and senior administration officials from five Danish municipalities. Based on Critical Discourse Analysis (CDA), the analysis shows how political discourses produce an ideal citizen identity and an understanding of the municipality as a consensus-based community, legitimizing these through idealized expounding of common cultural and historical symbols.